Phylogeography, geographic variation, and taxonomy of the Bent-toed Gecko Cyrtodactylus quadrivirgatus Taylor, 1962 from Peninsular Malaysia with the description of a new swamp dwelling species - Johnson, Chelséa B.; S. H., Evan Quah; Anuar, Shahrul; Muin, M. A.; Wood, Jr., Perry L.; Grismer, Jesse L.; Greer, Lee F.; Onn, Chan Kin; Ahmad, Norhayati; Bauer, Aaron M.; Grismer, L. Lee (Zootaxa, 2012)
A review of the taxonomic status of the Bent-toed Gecko Cyrtodactylus quadrivirgatus Taylor, 1962 based on a molecularphylogeny, scalation, and color pattern analyses indicate that it is composed of a single, recently expanding, widespreadpopulation with weakly supported phylogeographic substructuring with no discrete morphological differentiation betweenpopulations. However, based on sampling, significant mean differences in selected scale counts occur between some pop-ulations. The molecular phylogeny and morphological analysis strongly indicate lineage independence between a subsetof individuals from the Bukit Panchor, Penang population and their closest relative C. pantiensis Grismer, Chan, Grismer,Wood & Belabut, 2008 from southern Peninsular Malaysia. Furthermore, the analyses indicate that the individuals of thissubset are conspecific and not part of C. quadrivirgatus as previously suggested. Additionally, this subset is morphologi-cally distinct from all other Sundaland species of Cyrtodactylus, and as such is described herein as Cyrtodactylus payacola sp. nov.